In vitro and in silico cytotoxicity of hinokinin-loaded PLGA microparticle systems against tumoral SiHa cells. Issue 18 (8th September 2022) - de Lima, Regiane G.; Lisoni, Flavia C. R.; Picão, Thais B.; dos Santos, Fransérgio F.; Orenha, Renato P.; Borges, Alexandre; Molina, Eduardo F.; Parreira, Renato L. T.; e Silva, Márcio L. A.; Santos, Mario F. C.; de Laurentiz, Rosangela da S.
Abstract: This work aimed to synthesize poly (D, L-lactic-co-glycolic acid) (PLGA) microparticles containing hinokinin (HNK) and to evaluate their cytotoxic activity against tumoral SiHa cells and non-tumoral HaCaT cells. Hinokinin was incorporated into PLGA (PLGA-HNK) with an encapsulation efficiency of 84.18 ± 2.32%. PLGA and PLGA-HNK were characterized by SEM microscopy and showed spherical morphology with an average size of ∼3.33. Encapsulation efficiency was determined by a calibration curve using UV-vis spectroscopy. PLGA-HNK more active inhibiting proliferation of SiHa cells (IC50 = 14.68 µM) than free HNK (IC50 = 225.5 µM). In relation to HaCaT cells, PLGA-HNK showed no significant difference compared to the negative control. These results led to an increase in HNK bioavailability and thereby, biological activity. In silico prediction analysis suggests that HNK is cytotoxic against SiHa cells with E6 and MDM2 inhibition as possible main mechanism of action. Graphical Abstract: UF0001